Fluorescent pyridine phosphonium salts via transmutation of metallabenzenes - Yaowei Zhang; Feifei Han; Zhihong Yin; Yapeng Cai; Xiaoyan Zhang; Hong Zhang (Nature Communications)
Abstract Metallabenzenes are recognized as a unique class of aromatic compounds, not only of structural and theoretical interest but also as platforms to design powerful transformations. Here, we report the successful transmutation of a metallabenzene for pyridine synthesis. This ‘metal-to-nitrogen swapping’ process utilizes readily available ruthenabenzene phosphonium salts and commercially available 2-aminopyridines under mild conditions. The isolation of ruthena-azepines, containing a planar seven-membered aza-metallacycle, along with DFT calculations, supports the nitrogen insertion/metal deletion cascade driven by aromatization. Additionally, we investigate the tunable photophysical properties of the resulting pyridine phosphonium salts.